"Good Athletes Have Fun": a Foucauldian reading of university coaches' uses of fun - Avner, Z.; Denison, J.; Markula, P. (Sports Coaching Review, 2019)
Fun is deeply ingrained in the ways we talk about and understand sport: Having fun is what makes sport positive and healthy. Drawing on a Foucauldian perspective, we problematize how fun, a psychological construct, informs coaches` practices. Interviews with 10 varsity coaches from a Canadian university indicated that the coaches used fun to overcome the `grind` of physical skill training. In addition, fun was used to develop and naturalize a need for athletes` positive psychological traits and skills. In their training contexts, thus, the coaches clearly employed fun to reinforce their use of a number of dominant disciplinary training practices. As a result, instead of operating as a positive force for athlete engagement, the incorporation of fun further legitimized and perpetuated coaches` `normal` training practices.